Economic growth, energy consumption, and environment : assessing evidence from OECD countries - Shafiei, Sahar (Curtin University, 2013)
This thesis aims to investigate the impacts of renewable and non-renewable energy consumption on economic growth and CO2 emissions in OECD countries. The empirical results show that that both energy sources stimulate economic growth. Further, the empirical results support the existence of an environmental Kuznets curve between urbanization and CO2 emissions. Therefore, policies should be directed toward urban planning as well as substantial usage of renewable energy to mitigate climate change.